Student worksheets with virtual laboratory to train science literacy in acid-base learning - Yulisa Dwi Anggraeni; Achmad Lutfi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aimed to obtain Student Worksheets suitable for training students' scientific literacy. This research includes research and development. The research procedure carried out to develop this teaching material refers to the steps of the ADDIE model but is only carried out until the development stage and limited trials are carried out. The problem was carried out in one class that was randomly selected. Feasibility was tested based on validity, practicality, and effectiveness. An expert validator carries out the validity, and a score is determined using the mode. Validity results obtained a score of 4 with a very valid category on student worksheets 1 and 2. The results of the practicality analysis were viewed from the effects of student responses and observations of student activities. A practicality percentage of 90%-100% was obtained in the very practical category, then the results of observations of students' activities with relevant activities at meeting 1 amounted to 97.04%, and at meeting two amounted to 98.03%. From the two activity percentages, the relevant activity percentage obtained ≥ 61%, so it can be said that student worksheets are very practical. The results of the analysis of the effectiveness of student worksheets were measured based on the results of scientific literacy ability scores, which were analyzed using the t-test and obtained a significance value of 0.000 so that the developed student worksheets were said to be effective. Based on the results of the validation, practicality, and effectiveness analysis, it was found that the student worksheet with a virtual laboratory to train scientific literacy that was developed was feasible to use.